ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA SMP PADA MATERI SEGITIGA DAN SEGIEMPAT - Wiwik Widianti; Nita Hidayati (IKIP Siliwangi, 2021)
This study aims to analyze the level of mathematical literacy skills of junior high school students level 1, 2, and 3 on triangles and rectangles. This research was conducted on 24 students of class VIII one of the public schools in Cirebon Regency with a qualitative descriptive research method. The data collection technique used a mathematical literacy test in the form of material description questions of triangles and squares and field notes. The analysis technique used is the technique of Miles & Hubermen which includes three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that from the 4 mathematical literacy questions given, it was found that level 1 mathematical literacy skills had a fairly high percentage compared to other levels, namely 62.5%, level 2 mathematical literacy skills with a percentage of 21.9%, while mathematical literacy skills level The 3 percentages obtained were 9.7%. The results of this study indicate that students' mathematical literacy skills are still at level 1.